2013
DOI: 10.1016/j.gene.2013.01.062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of α-mating factor secretion signal mutations on recombinant protein expression in Pichia pastoris

Abstract: The methylotrophic yeast, Pichia pastoris, has been genetically engineered to produce many heterologous proteins for industrial and research purposes. In order to secrete proteins for easier purification from the extracellular medium, the coding sequence of recombinant proteins are initially fused to the Saccharomyces cerevisiae α-mating factor secretion signal leader. Extensive site-directed mutagenesis of the prepro region of the α-mating factor secretion signal sequence was performed in order to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 30 publications
1
106
0
2
Order By: Relevance
“…Several receptors, such as the wild-type M2 muscarinic receptor and A 2A R, showed reliable and reproducible expression, however much of the expressed proteins were present in the immature unprocessed form (without MFa cleavage) indicating that they had not been properly localized to the plasma membrane ( Figure 1-figure supplement 1). To improve the efficiency of production of mature, folded receptors, we made several modifications to the MFa sequence, based on biochemical and genetic precedents (Rakestraw et al, 2009;Lin-Cereghino et al, 2013) for improved processing efficiency ( Figure 1A, Materials and methods). was 0.42 nM in NaCl-containing buffer, while the K i for NECA was 210 nM in low ionic strength and 420 nM in KCl-containing buffer, in agreement with previous binding studies (Xu et al, 2011;Carpenter et al, 2016;Bertheleme et al, 2013) We developed a purification protocol for A 2A R from Pichia-derived membranes, in which we can solubilize and purify~0.5 mg of monodisperse biochemically pure wild-type A 2A R in dodecylmaltoside (DDM) detergent from 1 L of culture (Figure 1-figure supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several receptors, such as the wild-type M2 muscarinic receptor and A 2A R, showed reliable and reproducible expression, however much of the expressed proteins were present in the immature unprocessed form (without MFa cleavage) indicating that they had not been properly localized to the plasma membrane ( Figure 1-figure supplement 1). To improve the efficiency of production of mature, folded receptors, we made several modifications to the MFa sequence, based on biochemical and genetic precedents (Rakestraw et al, 2009;Lin-Cereghino et al, 2013) for improved processing efficiency ( Figure 1A, Materials and methods). was 0.42 nM in NaCl-containing buffer, while the K i for NECA was 210 nM in low ionic strength and 420 nM in KCl-containing buffer, in agreement with previous binding studies (Xu et al, 2011;Carpenter et al, 2016;Bertheleme et al, 2013) We developed a purification protocol for A 2A R from Pichia-derived membranes, in which we can solubilize and purify~0.5 mg of monodisperse biochemically pure wild-type A 2A R in dodecylmaltoside (DDM) detergent from 1 L of culture (Figure 1-figure supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA for wild-type human ADORA2A adenosine A 2A receptor was cloned into the pPICZ vector for expression in Pichia pastoris with a modified MFa secretion signal combining previous precedents (Rakestraw et al, 2009;Lin-Cereghino et al, 2013). Modifications to the MFa greatly increased the amount of fully-processed receptor present at the plasma membrane.…”
Section: Construct Designmentioning
confidence: 99%
“…for human serum albumin (HSA), human lysozyme, some fungal enzymes -see Gasser et al 2013). Earlier this year, two publications employing signal sequences only (Fitzgerald & Glick, 2014;Govindappa et al, 2014), as well as a mutant version of MFa (Lin-Cereghino et al, 2013), have been reported. Reasons for differences in secretion rates are manifold, but processing of the secretion leader, thermodynamic instability, misfolding, as well as misdirecting, are obvious; however, not yet understood in full detail.…”
Section: Introductionmentioning
confidence: 99%
“…9) [19]. The chosen αpre signal was just the pre-region of α-factor, which is believed to be important for interaction with the signal recognition particle, subsequent translocation into the ER, and folding of the nascent protein [20].…”
Section: Discussionmentioning
confidence: 99%